Hubungan Dukungan Sosial Teman Sebaya dengan Academic Burnout Siswa - Haulia, Natasya Putri; Febriani, Rahmi Dwi Febriani; Hariko, Rezki; Sari, Azmatul Khairiah; Putra, Febri Wandha (Jurnal Konseling Komprehensif: Kajian Teori dan Praktik Bimbingan dan Konseling, 2024)
This study was motivated by the phenomenon of academic burnout that occurs in students. Students experience symptoms of academic burnout such as boredom with schoolwork, falling asleep easily during lessons, ignoring assignments given by teachers, difficulty remembering material, unable to complete assignments so that their academic achievement decreases. One of the factors suspected of influencing student academic burnout is peer social support. This study aims to: (1) describe peer social support, (2) describe student academic burnout, (3) test the relationship between peer social support and student academic burnout. This study uses a quantitative method with a descriptive correlational research type. The population used in this study were 284 students in grade VII of the 2023/2024 academic year at SMP Negeri Kota Padang, the number of samples in this study was 167 students. Sampling used the proportional random sampling technique. Data collection used peer social support instruments and academic burnout instruments using the Likert model scale. Data were analyzed using descriptive statistical techniques and product moment correlation techniques. The results of this study indicate that (1) peer social support is in the moderate category with an average percentage of 66% (2) student academic burnout is in the low category with an average percentage of 49% (3) there is a significant relationship between peer social support and student academic burnout with a calculated r correlation value of -0.303 with a significance level of 0.000 at a weak relationship level. This means that if students have high peer social support, the lower the student's academic burnout. Conversely, the lower the peer social support, the higher the student's academic burnout. The urgency of this study is to have a value of benefit for teachers to be able to recognize student academic burnout. Based on the results of the study, guidance and counseling teachers can make policies and provide services such as information services, individual counseling services, and group guidance services to increase peer social support and reduce the level of high-category student academic burnout.